Immunohistochemical Characterization of the Chemosensory Pulmonary Neuroepithelial Bodies in the Naked Mole-Rat Reveals a Unique Adaptive Phenotype - Pan, Jie (PLoS One, 2014)
The pulmonary neuroepithelial bodies (NEBs) constitute polymodal airway chemosensors for monitoring and signaling ambient gas concentrations (pO(2), pCO(2)/H(+)) via complex innervation to the brain stem controlling breathing. NEBs produce the bioactive amine, serotonin (5-HT), and a variety of peptides with multiple effects on lung physiology and other organ systems. NEBs in mammals appear prominent and numerous during fetal and neonatal periods, and decline in the post-natal period suggesting an important role during perinatal adaptation. The naked mole-rat (NMR), Heterocephalus glaber, has adapted to the extreme environmental conditions of living in subterranean burrows in large colonies (up to 300 colony mates). The crowded, unventilated burrows are environments of severe hypoxia and hypercapnia. However, NMRs adjust readily to above ground conditions. The chemosensory NEBs of this species were characterized and compared to those of the conventional Wistar rat (WR) to identify similarities and differences that could explain the NMR’s adaptability to environments. A multilabel immunohistochemical analysis combined with confocal microscopy revealed that the expression patterns of amine, peptide, neuroendocrine, innervation markers and chemosensor component proteins in NEBs of NMR were similar to that of WR. However, we found the following differences: 1) NEBs in both neonatal and adult NMR lungs were significantly larger and more numerous as compared to WR; 2) NEBs in NMR had a more variable compact cell organization and exhibited significant differences in the expression of adhesion proteins; 3) NMR NEBs showed a significantly greater ratio of 5-HT positive cells with an abundance of 5-HT; 4) NEBs in NMR expressed the proliferating cell nuclear antigen (PCNA) and the neurogenic gene (MASH1) indicating active proliferation and a state of persistent differentiation. Taken together our findings suggest that NEBs in lungs of NMR are in a hyperactive, functional and developmental state, reminiscent of a persistent fetal state that extends postnatally.